Effect of B2O3 on the physical and mechanical properties of calcium fluoroaluminosilicate glass system - Mohammed Efa, Abdelkader; Matori, Khamirul Amin; Mohd Zaid, Mohd Hafiz; Che Abdullah, Che Azurahanim; Zainuddin, Norhazlin; Mayzan, Mohd Zul Hilmi; Kamis, Shahira Liza (Springer Science and Business Media, 2024)
Bioactive glasses containing boron oxide have attracted substantial attention owing to their unique attributes and the promising prospects they offer for biomedical uses. The study explores boro calcium fluoro alumino silicate (BCFAS) glass containing boron oxide, highlighting its potential in biomedical applications. The glass was synthesized through melt-water quenching with varying B2O3 ratios, utilizing CaO from clam shell and SiO2 from soda lime silica glass waste. The investigation examined the physical and mechanical properties of the resulting samples. Results showed that increasing B2O3 content caused a reduction in crystallinity, as confirmed by XRD analysis. The incorporation of B2O3 into the glass structure was further supported by the emergence of B‒O‒B and Si‒O‒B bonds observed in FTIR spectroscopy, which may potentially influence the glass's dissolution and degradation characteristics. However, higher B2O3 content also reduced density, impacting the mechanical properties. Vickers microhardness and compressive strength decreased due to the introduction of the BO3 unit, which increased the fragility of the glass. While enhancing glass-like behavior and potentially increasing bioactivity, the addition of B2O3 adversely affected its mechanical attributes. © The Author(s), under exclusive licence to Springer Nature B.V. 2024.